Immigrant women’s portraits: the socio-economic profile of the Greek Canadian women - Gavaki, Efrosini (The Greek Review of Social Research, 2003)
The paper explores the socio-economic status of women of Hellenic ethnic origin in Canada (both single and multiple). Such status was mostly looked at through the indicators of income, education and occupation as reported in the 1991 census. Greek women who arrived in Canada before WWII and the 1950’s-1970’s heavy Greek migration did not really enter the labour force. When they did, they, and their daughters, worked mostly at family business. However, their community and charity work was unsurpassed. As the Greek immigrant women who arrived in Canada during the 1950’s to 1970’s dominate the portrait of the group, they have overshadowed whatever inroads the descendents of the early arrivals had achieved. This last wave entered the host society at the lowest socio-economic levels such as contract workers for factories, as domestics, and as hospital workers. Upward mobility has been slow and hard. The 1991 data indicate that they rank low at the social status indicators. However, this portrait is expected to radically have changed during the decade of the 90’s. New immigration from Greece has come to an end; 1991 was the turning point when the Canadian born Greeks surpassed in numbers those born elsewhere, and; the 90’s decade has seen the retirement of the immigrants women from the labour force and the entrance of their educated and skilled daughters.